2014
DOI: 10.1097/qai.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Hepatitis C Infection With T-Cell Phenotypes in HIV-Negative and HIV-Positive Women

Abstract: Background Hepatitis C virus (HCV) viremia is thought to have broad, systemic effects on the cellular immune system that go beyond its impact on just those T-cells that are HCV-specific. However, prior studies of chronic HCV and circulating T-cell subsets (activation and differentiation phenotypes) in HIV-negatives used general population controls, rather than a risk-appropriate comparison group. Studies in HIV-positives did not address overall immune status (total CD4+ count). Methods We used fresh blood fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…HCV has been reported to have an impact on T cell phenotypes in HIV-1-infected persons. 43 Although there was no significant difference in HCV serostatus between the groups, there was a significant association of HCV seropositivity with CMV IgG levels among HIV-1 viremic women.…”
Section: Clinical Characteristics Of the Study Cohortmentioning
confidence: 84%
“…HCV has been reported to have an impact on T cell phenotypes in HIV-1-infected persons. 43 Although there was no significant difference in HCV serostatus between the groups, there was a significant association of HCV seropositivity with CMV IgG levels among HIV-1 viremic women.…”
Section: Clinical Characteristics Of the Study Cohortmentioning
confidence: 84%
“…HCV/HIV coinfection is known to be associated with lower CD4 counts and a smaller CD4-cell recovery [22,23] attributed to homeostatic alterations in CD4 subsets or thymic defects. [2426] Our data show a significant association of lower CD4 numbers with worse fibrosis suggesting that immune failure is a strong correlate of liver fibrosis in HCV/HIV coinfected patients.…”
Section: Discussionmentioning
confidence: 73%
“…[10,29] More recent studies have reported CD8 T-cell activation is not enhanced in HCV/HIV coinfected [11,24,30] and HCV/HIV coinfected subjects have activated CD4 T cells. [11,24] An earlier study in the WIHS cohort by Kovacs et al [29] reported elevated CD8 T-cell activation in HCV/HIV coinfected subjects, wherein HIV-1 disease in most women was at an early stage: almost 50% were untreated and only 7.7% were receiving HAART. In contrast, a more recent study in WIHS cohort by Kuniholm et al [24] assessing T-cell phenotype in HIV-infected women stratified by HCV RNA did not find CD8 T-cell activation in HCV/HIV coinfected women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic HCV infection has rarely been known to be associated with lymphopenia, but its immune modulatory effects have been increasingly recognised . One previous study reported CD4 + lymphopenia in 43% of 62 HCV‐related cirrhosis cases .…”
Section: Discussionmentioning
confidence: 99%